Implementation of Operand Decomposition and Carry Approximation for ECG Signal Denoising - T.R.Dinesh Kumar, Mr.; KMohanasundaram, Dr.; M.Anto Bennet, Dr.; Kishore Kumar, S.; Thangavel, M.; Venkatesh, M. (International Journal of Engineering and Technology, 2026)
A novel RNA based architecture topology that resulted more effective than prefix topology. Here, A tendancy to describe the stages in RNA prefix adders is divided and presents a modulo residue detection network that reduces error chances compared to previous approaches. Finally through FPGA based hardware synthesis performance is evaluated and latency variation is proved through exhaustive test bench simulation. For high speed design we carried multiply and Accumulate (MAC) using proposed adder and inner products are calculated through sequent addition.